2018
DOI: 10.1002/arch.21474
|View full text |Cite
|
Sign up to set email alerts
|

Heart mechanical and hemodynamic parameters of a beetle, Tenebrio molitor, at selected ages

Abstract: The physiological processes that occur during the aging of insects are poorly understood. The aim of this study was to describe the changes in contractile activity and hemodynamic parameters of the heart that take place as the coleopteran beetle, Tenebrio molitor, ages. The frequency of heart contractions in beetles that had just undergone metamorphosis (median 24.7 beats/min) was significantly lower than the frequency of heart contractions in older beetles. In 56% of beetles that were < 1 week of age, a patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…It has also been demonstrated that the majority of older wild-type flies exhibit non-rhythmic heart contraction patterns, including frequent asystole/bradycardia and ectopic beats (Ocorr et al, 2007b; Santalla et al, 2014). Similar changes in the heart rhythm have been detected in T. molitor beetles (Pacholska-Bogalska et al, 2018). In older beetles, more abnormalities in heart rhythm, arrhythmias, were detected.…”
Section: Beetles As Model Organisms In Biomedicinesupporting
confidence: 81%
See 2 more Smart Citations
“…It has also been demonstrated that the majority of older wild-type flies exhibit non-rhythmic heart contraction patterns, including frequent asystole/bradycardia and ectopic beats (Ocorr et al, 2007b; Santalla et al, 2014). Similar changes in the heart rhythm have been detected in T. molitor beetles (Pacholska-Bogalska et al, 2018). In older beetles, more abnormalities in heart rhythm, arrhythmias, were detected.…”
Section: Beetles As Model Organisms In Biomedicinesupporting
confidence: 81%
“…In older beetles, more abnormalities in heart rhythm, arrhythmias, were detected. In this group of beetles, the incidence of arrhythmia and the arrhythmicity index were higher than in a group of younger beetles (Pacholska-Bogalska et al, 2018). This finding suggests that the beetle heart preparations can also be used as a model in the studies on aging and for testing cardioactive drugs as well.…”
Section: Beetles As Model Organisms In Biomedicinecontrasting
confidence: 61%
See 1 more Smart Citation
“…Functional analogies at the molecular and cellular level between the myocardium of the insect and the mammalian heart were shown in the research on the fruit fly D. melanogaster , among others, by Bier and Bodmer [13] and Ocorr et al [14]. Nowadays, other insects, such as locusts ( L. migratoria ), stick insects ( B. extradentatum ), moths ( B. mori) or beetles ( T. molitor ) are used more and more often to evaluate the action of various bioactive substances, as well as to analyse the basis and the course of some diseases [15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The HR of T. molitor is often studied. Also arrhythmicity is present in beetles already at first week of life and its index during aging increases to 3.2 versus 0.2 (Pacholska‐Bogalska et al, 2018). An increase in diastolic intervals may accompany this development.…”
Section: Pacemaking Via Hcnmentioning
confidence: 99%